The case of the three rings - Erickson, John R., 1943- (Erickson, John R., 1943- Hank the Cowdog, 2014)
Slim must complete Uncle Johnny's "little job"--which has become more complicated than Slim signed up for--and race home in time to patch things up with Miss Viola, or their engagement may be over.